Kajian Literatur: Peran Teori Identitas Sosial dalam Pembentukan dan Reduksi Prasangka Antar Kelompok - Muhammad Difa Putra Adrila; Neviyarni S (PT. Hasba Edukasi Mandiri, 2025)
Intergroup prejudice remains a fundamental issue within multicultural societies, including Indonesia. Social Identity Theory (SIT) by Tajfel and Turner (1979) offers a comprehensive conceptual framework to understand how individuals construct self-concepts through group membership, which subsequently fosters ingroup–outgroup bias and prejudice toward other groups. This article aims to review, synthesize, and analyze empirical and theoretical research from the past decade concerning the relationship between social identity and prejudice. Literature findings confirm that strong social identity amplifies tendencies of ingroup favoritism and outgroup bias, while contextual factors such as threat, status, and intergroup contact serve as moderators that can intensify or reduce prejudice. Developments in theories such as Self-Categorization Theory and the Common Ingroup Identity Model have enriched intervention tools based on SIT, especially for multicultural education and cross-group dialogue. However, the reviewed literature also highlights the necessity for integrative approaches and contextual adaptation, particularly in local cultural settings like Indonesia. The article concludes that while SIT effectively explains the mechanisms of prejudice, its reduction strategies require combined theoretical models and contextually tailored practices.